2001
DOI: 10.1128/jcm.39.4.1217-1220.2001
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Diagnosis of Helicobacter pylori Infection and Real-Time Determination of Clarithromycin Resistance Directly from Human Gastric Biopsy Samples

Abstract: A novel PCR detection assay that amplifies the Helicobacter pylori-specific vacuolating cytotoxin gene (vacA) and thus enables rapid diagnosis of infection is described. Additionally, a real-time probe hybridization melting point analysis assay to detect all three mutations in the 23S rRNA gene associated with clarithromycin resistance was applied directly to antral gastric biopsy samples. Comparison with culture and an alternative PCR assay targeting the 16S rrn gene showed that the vacA assay was sensitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 26 publications
1
113
1
1
Order By: Relevance
“…The vacA gene, though also present in all strains, shows considerable polymorphism, 25 which could explain it to be less sensitive than ureC as a molecular diagnostic marker for H. pylori. 10,14 We found cagA to be present in 37% of the H. pylori strains in our study, which is in agreement with the low prevalences reported in Western populations. 26,27 There was a tendency towards better sensitivity for real-time PCR than conventional PCR, but the difference did not reach statistical significance.…”
Section: Articlesupporting
confidence: 82%
See 3 more Smart Citations
“…The vacA gene, though also present in all strains, shows considerable polymorphism, 25 which could explain it to be less sensitive than ureC as a molecular diagnostic marker for H. pylori. 10,14 We found cagA to be present in 37% of the H. pylori strains in our study, which is in agreement with the low prevalences reported in Western populations. 26,27 There was a tendency towards better sensitivity for real-time PCR than conventional PCR, but the difference did not reach statistical significance.…”
Section: Articlesupporting
confidence: 82%
“…Conventional PCR targeting the ureC, vacA and cagA genes was performed using PCR conditions as described elsewhere. 10,14,15 Realtime PCR for ureC was performed using the same primers as for conventional PCR and by constructing a TaqMan probe. Details of DNA primer and probe sequences are given in Table 1.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR amplifications were performed according to previously described protocols [35,36]. cagA and vacA genotyping cagA status was determined for H. pylori positive samples by polymerase chain reaction (PCR) using two different primers pairs as described previously [12,37] (Table 1).…”
Section: Detection Of H Pylorimentioning
confidence: 99%